2018
DOI: 10.1021/jacs.8b02013
|View full text |Cite
|
Sign up to set email alerts
|

Iron Redox Chemistry Promotes Antiparallel Oligomerization of α-Synuclein

Abstract: Brain metal dyshomeostasis and altered structural dynamics of the presynaptic protein α-synuclein (αS) are both implicated in the pathology of Parkinson's disease (PD), yet a mechanistic understanding of disease progression in the context of αS structure and metal interactions remains elusive. In this Communication, we detail the influence of iron, a prevalent redox-active brain biometal, on the aggregation propensity and secondary structure of N-terminally acetylated αS (αS), the physiologically relevant form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 51 publications
2
49
0
Order By: Relevance
“…Tetrameric NAc αS was expressed and purified as previously described [1] , [2] . Verification of the multimeric conformer was confirmed by BN-PAGE, and the associated native gel for the intact protein has been described in the related research article [1] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Tetrameric NAc αS was expressed and purified as previously described [1] , [2] . Verification of the multimeric conformer was confirmed by BN-PAGE, and the associated native gel for the intact protein has been described in the related research article [1] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Metal dyshomeostasis has long been linked to PD [18][19][20], and victims of PD present with increased cerebral iron levels and diminished levels of copper in affected regions of the brain. Although the precise roles of brain metals on the function of NAc αSyn have yet to be elucidated, we [10,[21][22][23] and others [9,24,25] have demonstrated how prevalent brain biometals modulate the structural outcome of NAc αSyn self-assembly pathways and influence both the potential and the extent of its aggregation.…”
Section: Introductionmentioning
confidence: 91%
“…Efforts are also being made to elucidate the participation of other molecules in the α-Syn altered dynamics. Namely, Abeyawardhane et al reported the contribution of oxygen and redox active iron in conformational change and oligomerization of α-Syn, which can be useful in understanding the mechanisms of its physiological and/or pathological role [13]. The strong ability of α-Syn to form complexes with other biomolecules such as lipid moieties and cholesterol has also been reported.…”
Section: Synucleins Family-new Insights and Prospectsmentioning
confidence: 99%